The Impact of Larger Scale Agricultural Investments on Communities in South East Asia: A First Assessment - James Zhan; Hafiz Mirza; Will Speller (Revue Internationale de Politique de Développement)
Since the mid-2000s, corporate sector investments in agriculture in developing countries have increased sharply, driven by rising commodity prices, the strategic concerns of food-importing countries, and commercial opportunities. Using the findings of fieldwork conducted by UNCTAD and the World Bank in countries across Africa and Asia, this chapter focuses on the impact of such investments on communities in South-East Asia. Relying on interviews with representative of the companies concerned and with members of local communities, as well as other stakeholders, carried out using a dyadic approach, the chapter provides detailed findings on the impact of investments in areas such as employment, incomes, land rights and the environment. It shows that both beneficial and negative consequences of agricultural investments can be traced to specific factors, such as decisions taken by investors (and governments) at the early stages of investment processes, the business models utilised, and investor-community relationships, as well as the degree to which responsible approaches are built into operations. The findings on Asia, as well as from the wider study on which this chapter is based, offer valuable information for governments, investors and civil society groups with regard to designing policies and practices, and to establishing relationships between these actors and monitoring areas relevant to the impact and performance of investments.